An Evaluation of Smart Clip Self-Ligating Bracket System: Comparison of Treatment Outcome and Patient Response between Self-ligating and Conventional Pre-adjusted Edgewise Appliance - Bhatia, Virag; S. Kalha, Anmol; Nanda, Smruti Bhushan (Orthodontic Journal of Nepal, 2014)
Introduction: A number of studies have been undertaken to evaluate the friction characteristics of self-ligating brackets, however there have been only few studies which have actually evaluated the clinical efficiency of these self-ligating brackets. Objective: To evaluate the clinical efficiency of Smart Clip self-ligating bracket in terms of treatment time, number of appointments, ABO score, and patient perception by comparing it with a pre-adjusted edgewise appliance system (MBT). Materials & Method: A prospective in vivo study in which twelve patients were bonded with Smart Clip self-ligating appliance and twelve patients were bonded with conventional pre adjusted edgewise appliance (MBT). The record of number of visits was maintained for each visit. At the end of treatment all 24 patients were asked to fill a questionnaire consisting of 10 questions. Post-treatment OPG and study models of all cases were evaluated for ABO score. Result: Average treatment time with Smart Clip self-ligating bracket was 4.5 months shorter than conventional pre-adjusted edgewise bracket. Mean number of appointments with Smart-Clip self-ligating brackets were 6.5 less than conventional pre-adjusted edgewise bracket. There was no significant difference in the quality of treatment with both groups having similar ABO scores. Patient perception to treatment in both the groups was also similar, except that patients with Smart Clip appliance system experienced more pain during wire insertion. Smart Clip group patients had greater difficulty in maintaining oral hygiene. Conclusion: Smart Clip bracket system is efficient in reducing the treatment time, but the quality of orthodontic treatment is similar to conventional pre-adjusted edgewise system. Patient perception for both the brackets is similar.